Connecting Residential Energy Efficiency and Carbon Emissions Reductions: MaineHousing’s Carbon Market Project - McCormick, Dale; Van Hook, Lucy (Maine Policy Review, 2008)
The transportation and residential sectors in Maine use a large proportion of fossil fuels, primarily petroleum products, and are a major contributor to greenhouse gas emissions. Dale McCormick and Lucy Van Hook in their article on MaineHousing’s carbon market project observe that energy use in buildings is the “next frontier” for emissions reductions. MaineHousing’s innovative program is aimed at generating and selling “emissions reduction credits” in the carbon market, through verified savings from weatherization and other energy measures. The funds generated can in turn be used to provide further weatherization assistance, as well as low-interest loans to homeowners for weatherization or installation of more energy-efficient systems.